Intra-articular pressure changes in rheumatoid and normal peripheral joints. - Gaffney, K (1995)
OBJECTIVE--To investigate the intraarticular pressure (IAP) dynamics of a spectrum of joints in rheumatoid and normal subjects in order to determine whether a reperfusion event is likely to occur at these sites. METHODS--IAP was measured in the metacarpophalangeal (MCP) (n = 8), wrist (n = 8), ankle (n = 4), and elbow joints (n = 4) of rheumatoid subjects, in addition to the MCP (n = 8), wrist (n = 6), and ankle joints (n = 1) of normal healthy controls, using the hand held portable 295-1 Intra-Compartmental Pressure Monitor System (Stryker, UK). RESULTS--Resting IAP was positive in all rheumatoid joints, and subatmospheric or weakly atmospheric in normal subjects (p < 0.01). Exercise produced an increase in IAP in rheumatoid subjects only (p < 0.01). The addition of saline to normal joints mimicked the IAP changes seen in the rheumatoid group. CONCLUSION--These observations suggest that increased resting IAP is a marker for chronic joint inflammation. The IAP increase seen in the rheumatoid group during exercise supports the concept of hypoxic reperfusion mediated joint injury.